MECHANISMS FOR FLUORIDE-PROMOTED DISSOLUTION OF BAYERITE [β-AL(OH)3(S)] AND BOEHMITE [γ-ALOOH]: 19F-NMR SPECTROSCOPY AND AQUEOUS SURFACE CHEMISTRY - A GENERALIZATION ON THE DISSOLUTION RATES OF MINERALS - Nordin J.P.; Sullivan D.J.; Phillips B.L.; Casey W.H. (My University, 1999)
Some reactions that control the dissolution of bayerite [β-Al(OH)3(s)] and boehmite [γ-AlOOH] were identified by comparing the adsorption chemistry, the dissolution rates, and solid-state 19F-NMR spectra of the reacting surfaces. The 19F-NMR spectra of bayerite distinguish two sites for fluoride reaction that vary in relative concentration with the total adsorbate density. One resonance at -131 ppm is assigned to fluoride bridges and the other resonance at -142 ppm is assigned to fluoride at terminal sites. These same resonances are observed on boehmite, in addition to a third resonance at -151 ppm that is tentatively assigned to aqueous AlFn(H2O)6-n(3-n)+(aq) complexes in pores. Peak broadening due to dipolar coupling between surface fluorides at high loading indicates that these sites are in close proximity.A consistent picture of dissolution is derived by considering the 19F-NMR results, the aqueous experiments, and information derived from the studies of aqueous complexes, particularly studies of the dissociation mechanisms of aqueous multimers. Both fluoride and adsorbed protons enhance the dissolution rates via a series of pathways that may be coupled to one another, and there is a profound dependence of the rate on the concentration of adsorbed protons and adsorbed fluorides. Particularly important are fluoride-substituted bridges and sites where aluminum atoms are bonded to several terminal fluorides or hydroxyls. These results illustrate that it is possible to test hypotheses about molecular-scale processes if adsorption studies are coupled to spectroscopy and ligand-promoted dissolution experiments where reaction via different pathways can be distinguished.